Situational personality and burnout syndrome in workers of a rehabilitation center - Rodríguez Ramírez, María del Carmen (2020)
Objective: To demonstrate the correlation between the dimensions of burnout syndrome and the factors of situational personality in workers of a rehabilitation center. Materials and methods: A non-experimental, cross-sectional and correlational study conducted with 194 participants belonging to the health and administrative personnel, as permanent or temporary employees, of the Instituto Nacional de Rehabilitación, who were individually instructed to answer the Maslach Burnout Inventory (MBI) and the Situational Personality Questionnaire (SPQ). Results: The health personnel showed higher levels of psychological burnout than the administrative personnel. Psychological burnout was mainly associated with factors such as anxiety, emotional stability, aggressiveness, self-confidence and self-assurance, whereas the personal realization (PR) dimension was related, to a greater extent, to scales of cognitive control, efficacy, aggressiveness, self-confidence and self-assurance. Conclusions: The study showed that the burnout syndrome is related to some characteristics of situational personality.